Pharmacokinetics of cannabidiol and its two main phase I metabolites in Connemara ponies - Wermer, Kata; Korbacska-Kutasi, Orsolya; Berkecz, Róbert; Csupor, Dezső; Ágh, Nóra; Sztojkov-Ivanov, Anita; Cserhalmi, Dániel (Frontiers in Veterinary Science, 2025)
IntroductionCannabidiol (CBD) has shown potential therapeutic benefits in veterinary medicine, but further investigations are needed to establish its pharmacokinetics and therapeutic dosing in horses and ponies. The present study aimed to investigate the pharmacokinetic properties of CBD in Connemara ponies following oral administration of CBD oil.MethodsTen healthy ponies received a single oral dose of CBD oil at 2 mg/kg. Blood samples were collected before dosing and up to 16 days post-administration, with physical examinations conducted at baseline and at 8, 12, and 24 h post-dose. Additional blood samples were taken at baseline and 24 h for hematological and biochemical analyses. Targeted UHPLC–MS/HRMS measurements quantified CBD and its metabolites, 7-hydroxy-CBD (7-OH-CBD) and 7-carboxy-CBD (7-COOH-CBD).ResultsThe CBD oil was well-tolerated, with no side effects. A significant decrease in heart rate was observed after 24 h. Changes in hematological and biochemical markers included elevated urea, slight increases in chloride, Gamma-glutamyl transferase, Total bilirubin, Lactate dehydrogenase, and a minor reduction in WBC count. CBD was detectable in 4 ponies on day 7, but none on day 12. The 7-COOH-CBD metabolite remained detectable up to day 16 in all subjects. The pharmacokinetic parameters for CBD were Cmax = 31.472 ± 8.080 ng/mL, tmax = 2.111 ± 0.928 h, t1/2 = 12.563 ± 3.054 h, and Vz/F = 198.757 ± 49.123 L/kg.DiscussionThe pharmacokinetic characteristics of CBD observed in the present study are consistent with previous research in warmblood horses and provide a foundation for future studies to evaluate the therapeutic efficacy and long-term safety of CBD in ponies.